Co-precipitation technique to prepare BiTaO4 powders - Muthurajan, H.; Gupta, U. N.; Rituraj, B.; Rao, N. Koteswara; Pradhan, Sivaram; Radha, R.; Ravi, V. (Materials Letters, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure ultrafine single phase BiTaO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. This precursor, on heating at 600 degrees C, produced product phase. This is the lowest temperature for the formation of BiTaO4 phase so far reported in the literature. For comparison BiTaO4 powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: BiTaO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis of SrNb2O6 and SrTa2O6 using hydroxide precursor - Muthurajan, H.; Kumar, H. H.; Koteswara Rao, N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Ravi, V. (Materials Letters, 2008)
SrNb2O6 (SN) or SrTA(2)O(6) (ST) compounds were prepared at low temperatures for the first time from hydroxide precursors. A simple procedure of mixing commercially purchased strontium hydroxide and niobium (or tantalum) hydroxide thoroughly together and heating at a low temperature (<400 degrees C) produced SrNb2O6 (SN) or SrTa2O6 (ST) powders. This is the lowest temperature so far reported for the formation of these phases. These materials are potential candidates for ferroelectric and electro-optic applications. The reaction sequence and evolution of the phase formation were investigated by X-ray diffraction (XRD) studies. The average particle size and morphology of these powders were studied by scanning electron microscopy (SEM). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction